The unintended consequences of COVID‐19 public health measures on health care for children with medical complexity. (30th January 2022) - Baumbusch, Jennifer; Lloyd, Jennifer E. V.; Lamden‐Bennett, Shawna R.; Ou, Christine
Abstract: Aim: The aim of this work is to explore the unintended consequences of pandemic public health measures on health care service usage by children with medical complexity. Background: Medical complexity is characterized by the presence of complex, chronic conditions requiring specialized care, substantial health needs, functional dependence and/or limitations, and frequent health care usage. Children with medical complexity are among the highest users of paediatric health care services. Methods: A web‐based, cross‐sectional survey was conducted in British Columbia, Canada, between August and September 2020. Inclusion criteria were (a) parent/guardian of at least one child (age 0 to 18 years, inclusive) with medical complexity and (b) residence in British Columbia. A convenience sample of 156 parents completed the survey. Data were analysed using a series of descriptive analyses (frequencies, cross‐tabulations) and inferential analyses (binary logistic regressions). Results: Respondents provided information for 188 children with medical complexity. Access to allied health therapies (physio, occupational, and speech and language) and medical specialists drastically declined in the initial months of the pandemic, with a shift from in‐person to virtual platforms for these aspects of care. Regression modelling indicated that age and family structure influenced decisions to use in‐patient hospital services. Conclusions: Public health measures implemented in the initial months of the pandemic decreased access to health care services for children with medical complexity. The long‐term ramifications of these measures are unknown. Family structure was found to influence decisions to avoid accessing Emergency Department care. Given the volume of services used by these children, paediatric hospital leaders need to take their unique needs into consideration in disaster planning to ensure minimal disruptions in care.